Effects of continuous positive airway pressure on apnea-hypopnea index in obstructive sleep apnea based on long-term compliance - Stuck, Boris; Leitzbach, Sarah; Maurer, Joachim T. (Sleep and breathing, 2012)
Purpose: Although continuous positive airway pressure (CPAP) is the gold standard in the treatment of obstructive sleep apnea (OSA), its effectiveness depends on the regular use. In this retrospective study, the effectiveness of CPAP with regard to the reduction of the apnea-hypopnea index was calculated based on individual adherence data extracted from a cohort of patients with OSA - Methods: The electronic database was analyzed for follow-up visits of patients receiving CPAP for OSA. The following information was extracted the charts of 750 patients: apnea-hypopnea index (AHI) at diagnosis, AHI with CPAP, duration of therapy, hours of CPAP use, and subjective hours of sleep. Eighty-two successfully treated and stable CPAP patients (AHI/Epworth Sleepiness Scale (ESS) at baseline 35.6 ± 22.1/10.5 ± 5.1) could be further evaluated. Results: Mean AHI under CPAP was 2.4 ± 2.5 with an ESS of 6.9 ± 4.2. Subjective hours of sleep were 6.5 ± 1.1. The average treatment period was 584.6 ± 566.5 days (3,800 h of sleep). Mean hours of use was 2,712 ± 3,234 (4.69 ± 2.42 per night). This leads to the following calculated measures: hours of sleep without CPAP, 1,088; number of respiratory events with CPAP, 6508.8; number of respiratory events without CPAP, 38,732.8; total number or respiratory events, 45,241.6; average AHI, 11.91.Conclusions: Even in an ideal group of patients, CPAP cannot eliminate respiratory events due to limited adherence. Adherence needs to be taken into account when comparing the effects of CPAP on the AHI with alternative treatment methods, especially those with 100% adherence (e.g., surgery).